Distant metastasis of salivary gland cancer: Incidence, management, and outcomes. Issue 10 (25th February 2020) - Mimica, Ximena; McGill, Marlena; Hay, Ashley; Karassawa Zanoni, Daniella; Shah, Jatin P.; Wong, Richard J.; Ho, Alan; Cohen, Marc A.; Patel, Snehal G.; Ganly, Ian
Abstract : Background: Distant metastases (DMs) are the primary cause of treatment failure in patients with salivary gland carcinoma. There is no consensus on the standard treatment. Methods: Patients with DMs were identified from an institutional database of 884 patients with salivary gland cancer who underwent resection of the primary tumor between 1985 and 2015. Survival outcomes for patients with DMs were determined with the Kaplan‐Meier method. Univariate and multivariate analyses were performed to identify factors associated with DM. Results: Of the 884 patients identified, 137 (15%) developed DMs during follow‐up. Most of the primary tumors (n = 77 [56%]) were located in a major salivary gland. At clinical presentation, 53% of the tumors were classified as T3 or T4, and 32% had clinical node metastases. The median time to DM was 20.3 months. The factors associated with shorter distant recurrence–free survival were male sex, high‐risk tumor histology, and advanced pathological T and N classifications. Patients with bone metastases had a lower survival rate than patients with lung metastases. The total number of DMs in a patient was inversely associated with survival. Patients who underwent surgical resection of DMs had a significantly higher 5‐year rate of metastatic disease–specific survival than patients who underwent observation or nonsurgical treatment (44%, 29%, and 19%, respectively; P  = .003). Conclusions: In patients with DMs of salivary gland carcinoma, survival is negatively associated with high‐grade histology, bone DMs, and the total number of DMs. Metastasectomy can help to lengthen disease‐free survival. Abstract : Outcomes for metastatic salivary gland tumors are driven by the pathology, site, and number of distant metastases. Metastasectomy offers the benefit of long disease‐free survival for select patients.